TUBUH, HABITUS, DAN NGENG DALANG DAN PENGRAWIT WAYANG - St. Hanggar Budi Prasetya (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2008)
Body, Habitus, and Bourdieu’s theory have long been a topic of research in sociol- ogy of art.  Pierre Bourdieu’s work is widely viewed as a fruitful approach to both theory and  research on the body as Bourdieu links agency with structure through the process of habitus.  Bourdieu’s concept of habitus illuminates the circular pro- cess whereby practices are incorporated within the body, only then to be regener- ated through the embodied  work and competence of the body.   This research explores the process embodiment on puppet master and gamelan musicians.  Ngeng is the most important concept for gamelan musician to play and appreciate gamelan music.   The disciplined and rehearsed body of  the puppet master and gamelan musician is one of the most significant resources in the conduct of gamelan music. In this paper I explore some of these issues to make sense of  embodied work or ngeng of gamelan music performance drawing on my ethnography of  the shadow puppet theatre. Key words: ngeng, habitus, mlèsèd, nggandhul.